(3efM GdSejY HTQM JdejM GdHOjY HeOjM GdTajYs - (3Rjf GdOjf YHO GdQMef Hf CMeO Hf Ydj GdMejOis; (3YHO GdQMef Hf CMeO Hf Ydj GdMejOj GdeUQj,J (B1005 (3g` s ((3Rjf ESeGYjd Hf CMeO GdcQOi s)
(3ChdgG (B:s
(3CeG HYO aEf GdYde CaVd MdjI HgG GdeQD JMdi s
(3BNQgG (B:s
(3hGHf GdebQi hGdSjhWi gPG GdfhY ai BNQ HOjYGjGJgG hHjJ GdhLjg s
(3JcQQ CjVkG JMJ Qbe (B92 (3HdGZIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs